Drug tapering in animal research: current practices and challenges - Zhang, Yatong; Chen, Mengrui; Jiang, Tongtong; Fu, Qianfang; Ma, Rong; Nie, Lianghui; You, Yuqiong; Gao, Shuqi; Rong, Ping (Frontiers in Pharmacology, 2025)
PurposeTo synthesize and summarize the scope and protocols of drug tapering in existing animal studies, providing a reference for standardized tapering interventions in future research.MethodsUtilizing a scoping review framework, a systematic search was conducted in PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Data Knowledge Service Platform (Wanfang), China Science and Technology Journal Database (VIP), and China Biomedical Literature Service System (SinoMed) for studies on drug tapering in animal experiments published up to May 1, 2024. Key data such as disease type, drugs used, and tapering methods were extracted and analyzed.ResultsNineteen studies were included, addressing a range of diseases including respiratory issues, oncology, nephrology, neuropsychiatric disorders, fractures, organ transplantation, and perioperative pain. Only one study commenced tapering upon the emergence of drug toxicity, while the others did not explicitly state the timing of tapering. Tapering methods identified included reducing single drug doses, decreasing administration frequency, and intermittent dosing. The outcomes of tapering were classified into drug discontinuation, low-dose maintenance, and drug substitution, with all studies reporting the effects post-tapering.ConclusionThe methods of drug tapering in animal studies are influenced by multiple factors, including disease characteristics, treatment duration, animal tolerance, and specific goals. There remains a need for further refinement in tapering schedules, methods, and milestones, and the establishment of relevant evaluation metrics to better define tapering timing.